If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11t + -5b = 0 Reorder the terms: -5b + 11t = 0 Solving -5b + 11t = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-11t' to each side of the equation. -5b + 11t + -11t = 0 + -11t Combine like terms: 11t + -11t = 0 -5b + 0 = 0 + -11t -5b = 0 + -11t Remove the zero: -5b = -11t Divide each side by '-5'. b = 2.2t Simplifying b = 2.2t
| -4/5x-14=-2 | | u-6/7=6-5u+6/6 | | 5v^2-2v-7=0 | | z-2/7=-3/14 | | 32x^2=5x^2 | | 7x-6y=-10 | | 4x-2(x-3)=-4+5x-11 | | u-6/7=6-5u+6 | | 2x^2+4x-16y=0 | | 2(z+3)-14= | | 10b-45=3(-15) | | 7-5u=-2 | | 9(3y-9)= | | 75+2n=5.75n | | 4(-6)=3(w+1) | | -2(x+3)=16 | | 11/22x=88 | | x^2+x=-7.75 | | x^2/0.100-x | | 2lgx=lg(9x-20) | | -42x^2-47x+51=0 | | 57=2c+7.5c | | 5x/4-1/3=3 | | lgx=lg(9x-20) | | (y-4)/(y^2-16) | | 3x+10-4x-33=108-16x-100 | | 8(5-s)/5=-2s | | 7x-4=4x-58 | | 2(2z-1)-2(2-3z)=12 | | 5/14+2/14 | | 21=6(x-3) | | log(x+10)=1+log(4x-3) |